RUNWAY END SAFETY AREA: OVERRUN AND UNDERSHOT SAFETY RISK ANALYSIS - Paquita, Dzakia; Persadanta, Pintanugra; Sari, Anggi Nidya (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2024)
An airport is a complex facility for passenger and cargo processing, aircraft arrival, departure, and maintenance. Ensuring safe and comfortable flights for its passengers requires implementing aviation security and safety improvements in tandem with the growing number of aircraft in operation. Aviation operators and regulators are always focused on issues and potential incidents that jeopardize aviation safety and security, particularly during the landing and takeoff phases of flight, which include overrun and undershoot occurrences. Therefore, a study is required to determine the event’s probability. By adopting research methods that have been developed by the European Aviation Safety Agency (EASA), this research aimed to analyze the risk of overrun and undershoot at Sultan Syarif Kasim II Airport (SSK II) and Raja Haji Fisabilillah Airport (RHF). The research method is quantitative by comparing data collected with the Target Level of Safety (TLS), which is quantified and recommended by the aviation authority International Civil Aviation Organization (ICAO) and the British Civil Aviation Authority (CAA UK), where the acceptable TLS according to ICAO is 6.6 x 10-7 while according to the UK CAA it is 4 x 10-7. The result showed that the probability value of overrun and undershoot at SSK II Airport averages 0.66 x 10-7 and 2.98 x 10-7 at RHF Airport. This indicates that at RHF Airport, there is a higher possibility of overrun and undershooting risk frequency than at SSK II Airport. The fact that RHF Airport has just one RESA is the primary element affecting the high-risk likelihood at RHF Airport. The chance of overrun and undershoot occurrence frequency dropped to an average of 2.06 x 10-7 after simulating RESA compliance per ICAO regulations.